If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7m + 7 = -14 Reorder the terms: 7 + -7m = -14 Solving 7 + -7m = -14 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -7m = -14 + -7 Combine like terms: 7 + -7 = 0 0 + -7m = -14 + -7 -7m = -14 + -7 Combine like terms: -14 + -7 = -21 -7m = -21 Divide each side by '-7'. m = 3 Simplifying m = 3
| m(3.14)=3 | | 9*(4*8+10)+2= | | x+-8=35 | | .33(6x-9)=-1.5(4x-5) | | d^3-24d=-2d^2 | | 20+7m=5+10m | | d^3-24d=-2d^2 | | .33(6x-9)=-1.5(4x-5) | | d^3-24d=-2d^2 | | 7[6-y]=-3[y-2] | | -L=-8 | | -L=-8 | | -L=-8 | | -L=-8 | | -L=-8 | | -L=-8 | | -L=-8 | | -L=-8 | | -L=-8 | | -L=-8 | | -L=-8 | | -L=-8 | | -L=-8 | | -L=-8 | | -L=-8 | | -L=-8 | | -L=-8 | | -L=-8 | | -L=-8 | | -L=-8 | | -L=-8 | | -L=-8 |